The effects of multiple intelligences theory on learning success: A meta-analysis in social science - Ahmad Syafii; Imam Machali; Nur Hidayanto Pancoro Setyo Putro; Heri Retnawati; Hafidh 'Aziz (Institute of Advanced Engineering and Science, 2022)
Scholars have widely discussed meta-analysis studies on the theory of multiple intelligences. However, no research explicitly discusses the theory of multiple intelligences in the development of social science. This study determined the effectiveness of multiple intelligences on learning achievement in social studies. For this reason, researchers compiled a study that has been carried out to determine the effectiveness of multiple intelligences in meta-analysis. This study used a meta-analysis method. There are six articles used in the study based on the inclusion-exclusion criteria. The meta-analysis findings revealed that multiple learning intelligence had a modest and optimistic impact on students’ social science performance. This study also revealed the magnitude of the effect of multiple intelligence-based learning based on moderator variables at the level of education, treatment implementation time, and type of subject. The research findings provide suggestions for the development of research on multiple intelligence studies in the future.